Awareness of hepatitis C virus transmission routes among patients, their household contacts and health care staff: does perception match the reality? - (:unkn) unknown (My University, 2009)
BACKGROUND/AIMS: The worldwide seroprevalence of hepatitis C virus infection is around 3%. Since there is no effective vaccine, a major effort should be given to counselling both HCV-infected patients and those at risk of infection. Our aim was to determine the awareness of the transmission routes of hepatitis C virus in health care staff (HC staff), HCV-infected patients and their household contacts. METHODS: A reliable and valid self-report inquiry consisting of 14 questions was completed by 397 HC staff (75 first-year, 75 last-year medical students, 89 dentists, 71 pharmacists, 87 nurses), 68 HCV-infected patients and 62 household contacts. All subjects were asked about the various modes of transmission of hepatitis C virus. RESULTS: Ninety-seven percent of the HC staff, 85% of hepatitis C virus patients and 90% of household contacts were aware of the parenteral transmission of hepatitis C virus. Ninety percent of HC staff, 54% of hepatitis C virus patients and 66% of household contacts admitted the role of sexual transmission, with significant difference between the subgroups of HC staff (p<0.05). Fifteen percent of the first-year medical students did not consider sexual contact as a mode of transmission. Sharing personal items such as toothbrushes, razors and nail scissors were considered as risk factors for transmission by 94% of HC staff, 44% of hepatitis C virus patients and 71% of their household contacts. Skin contact, sharing clothes and using the same toilet were considered hazardous by 18%, 14% and 26% of the HC staff, respectively. Skin contact and using the same toilet were considered as risk factors (and/or were unknown) by 30% and 44% of the hepatitis C virus patients and by 36% and 51% of the household contacts, respectively. CONCLUSIONS: Transmission of hepatitis C virus by blood and blood products was better recognized in all groups tested, but the other means of infection were either overestimated (skin contact, sharing toilet and clothes) or under-recognized (blood-contaminated objects). More vigorous education programs are needed to increase awareness of hepatitis C virus in various risk groups in our country.
Keywords: Adult; Female; Humans; Middle Aged; Surveys and Questionnaires; Aged; Aged, 80 and over; Adolescent; Male; Young Adult; Health Knowledge, Attitudes, Practice; Family; Attitude of Health Personnel; Risk Factors; Students, Medical; Pharmacists; Dentists; Disease Transmission, Infectious; Hepatitis C; Nurses